Swaziland Engaging the Private Sector in Education : SABER Country Report 2016 - Chen, Callista (World Bank, Washington, DC, 2017)
This report presents an analysis of how effectively the current policies in Swaziland engage the private sector in basic (primary and secondary) education. The analysis draws on the engaging the private sector (EPS) framework, a product of the World Bank’s systems approach for better education results (SABER). SABER-EPS research in Swaziland has found that at both the primary and secondary levels, quality, and equity are challenges. The private sector plays an increasingly significant role in education at both levels. Based on a review of existing policies, SABER-EPS offers the following recommendations for Swaziland to enhance private sector engagement in education in order to meet the challenges of access, quality, and equity: (1) empower parents to make informed educational choices, while providing additional support to disadvantaged groups; (2) strengthen accountability mechanisms to ensure that all students receive a quality education; and (3) strengthen the policy environment for the non-state sector to promote transparency and an adequate supply of school places. The report provides an overview of SABER-EPS findings, followed by a description of the basic education system in Swaziland that focuses on the private sector and government policies related to the private provision of education. The report then benchmarks Swaziland’s policy environment utilizing the SABER-EPS Framework and offers policy options to enhance access and learning for all children in primary and secondary school.